Lexico-Semantic Group “Clothes” in Modern Russian Language: Theoretical and Methodical Guidelines (Proceedings of Southern Federal University. Philology, 2019)
Inga Yu. Abramova (Vladimir, Russian Federation)In the present study an attempt is made to formulate the basic theoretical provisions concerning the structure and functioning of the lexical-semantic group as a way to systematize the semantic space of the Russian language of the XXI century on the example of clothes discourse. The study is based on the analysis of 500 units extracted from more than 2,500 contexts presented in both print media and onlinepublications. In the course of the work the author reveals several essential features concerning the structure of lexical-semantic group. So, in addition to such characteristics as the similarity of the word paradigm based on the minimal integral element of meaning of a number of differential, bearing the “typical” character, the hierarchical principle of construction of the system, lexical-semantic group “Clothes” is characterized by a certain kind of lexical and grammatical features. Among the latter, we have identified the polynomial (the number of nominations in some cases exceeds the number of denotations), word-formation productivity on the example of composite nominations, as well as the active process of borrowing elements with subsequent lexical and grammatical adaptation in the modern Russian language. In addition, the author pays special attention to the combination of linguistic and extra-linguistic features of the functioning of the analyzed units as a result of creative and cognitive activity of the modern Russian linguistic personality, as well as lexical and grammatical processes, which are the result of the development of various branches of industrial production, the emergence of new realities of reality, requiring appropriate nominations, intercultural interaction between Russia and the countries of East and West.Key words: grammatical meaning, denotation, differential element of meaning, categorical-lexical (integral) element of meaning, lexical-semantic group, polynomial, composite nomination.DOI 10.23683/1995-0640-2019-1-83-90